Photocatalytic degradation of dyes by novel electrospun nanofibers: A review. (February 2023) - Sarkodie, Bismark; Amesimeku, Jeremiah; Frimpong, Charles; Howard, Ebenezer Kofi; Feng, Quan; Xu, Zhenzhen
Abstract: Textile industry is a significant contributor of wastewater, which contains pollutants including dye and other chemical substances. The release of thousands of tons of dye used in textile processing and finishing into natural streams and aquatic bodies present dire harm to the environment. In response to environmental concerns, a number of research have been done using low-cost technology to produce absorbents that can remove dyes from water bodies. Distinct techniques such as adsorption, enzymatic and photocatalytic degradation, etc. have been employed to remove dyes. In the last few decades, photocatalysis, a simple and green strategy, has emerged as the most valuable and recent principle that deals with wastewater treatment, using uniquely fabricated nanomaterials. Among them, rapid and versatile electrospinning methods have been used for the construction of a large surface area, hierarchical and reusable nanofibers for environmental remediation. As a flexible and fast fabrication method, reviewing the use of electrospun photocatalytic nanofibers, influential parameters in electrospinning and their effectiveness in the generation of oxidizing agents are a promising platform for the fabrication of novel nanomaterials in photocatalytic degradation of dyes. This review discusses techniques for dye removal, electrospun nanofibers, their fabrication and application in photocatalysis; mechanism of photocatalytic degradation, and challenges and suggested remedies for electrospun nanofibers in photocatalysis. Graphical abstract: Image 1 Highlights: Photocatalytic degradation is an effective and green strategy for removal of textile dyes. Electrospinning route is employed in fabricating reusable electrospun hybrid nanofibers. Good heterojunction in electrospun photocatalytic nanofibers positively influence their mechanism. Present challenges and remedies in electrospun photocatalytic nanofibers are proposed.